Optimization of technological modes of cupola melting according to the criterion of maximum combustion temperature - Demin, Dmitriy (Technology audit and production reserves, 2025)
The object of research is the combustion temperature in the cupola furnace. The problem under study was the complexity of predicting the temperature as a function of the control parameters of the melting. In the study, the control parameters were selected as the temperature of the air heating blown into the tuyeres and the completeness of fuel combustion. Using orthogonal experimental planning, a mathematical model was constructed in the form of a second-order polynomial, which allowed to identify the patterns of influence of each control factor on the resulting value – the combustion temperature. The resulting mathematical model allowed to find out that both input variables are significant. However, if the nature of the influence of the air heating temperature on the combustion temperature is linear, then the completeness of combustion affects nonlinearly. The accuracy of the model turned out to be satisfactory, because all experimental data fell within the confidence intervals with a confidence probability of P=0.99. This allows to state the possibility of using the constructed model to predict the combustion temperature within the planning area. The ridge analysis of the response surface established that the theoretical maximum value of the combustion temperature at the boundary of the planning area is about 3000 °C. This corresponds to the values of the input variables Tair≈1120 °C and η0≈82 %. However, due to the fact that ensuring the air heating temperature at the level of 1120 °C may encounter technical complexity of implementation, the following values of the input variables can be recommended: Tair=783–1060 °C, η0=71–80. They provide combustion temperatures in the range of 2690–2980 °C, i. e. values close to the suboptimal one determined by the ridge analysis. These data allow making adjustments to the melting process, including being used for further searching for optimal melting control. The obtained solutions can be used in iron foundry shops of industrial enterprises equipped with cupola furnaces.